Mapping of agricultural ecological zones (AEZ) for Nineveh Governorate (NTU Journal of Agriculture and Veterinary Science, 2024)
The research aims to develop a map of the agricultural environmental areas of Nineveh Governorate using remote sensing (RS) and the Geographic Information System (GIS) techniques. The study area located between longitudes 25 41 and 15 44 east and latitudes 15 34 and 3 37 north with an area of 37,323 km2.The map of agricultural ecological zones was derived by projecting five landform classes combined with seven soil mapping units, 9 types of land uses, 4 agro-climatic zones and hydrological map resulting in nine classes of an agricultural environmental map that included mountainous lands , urban areas, rugged areas with irrigated lands, irrigated lands, solid lands and residential areas, rainfed lands\1, natural pastures, rainfed lands\2, irrigated lands, irrigated and rainfed lands, with ratios reaching at rates of (2.28, 8.14, 10.49, 9.95, 15.05, 30.16, 19.01, 2.03, 2.88) % for each, respectively.